Analisis Kepatuhan Pengguanaan Obat Tuberkulosis Pada Penderita TB Paru Di UPT RS Paru Sumatera Utara Tahun 2023 - Tinambunan, Sarma; Manurung, Kesaktian; Sipayung, Rosetty; Nababan, Donal; Gultom, Rumondang (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Pulmonary tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a pressing global health issue, with high incidence and mortality rates. Treatment adherence is a key factor in the success of TB therapy. This study analyzes the factors influencing adherence to TB medication among pulmonary TB patients at UPT Lung Hospital of North Sumatra. The study employed a cross-sectional design with an analytical survey approach. The research sample consisted of 120 pulmonary TB patients undergoing treatment. Data were collected through questionnaires, medical records, and secondary sources and analyzed using the Chi-Square test and logistic regression. The results showed that education level (p-value = 0.03), employment status (p-value = 0.03), knowledge level (p-value = 0.00), and family support (p-value = 0.05) had a significant relationship with adherence to TB medication. Meanwhile, age (p-value = 0.91) and gender (p-value = 0.59) did not show a meaningful relationship. Multivariate analysis identified knowledge and family support as the dominant factors influencing adherence. These findings suggest that education-based interventions and enhanced family support can improve TB treatment adherence. This study recommends developing public health programs to empower patients and their families in TB control efforts.